Ответы и объяснения

2013-12-24T15:57:26+00:00
{x + y + xy = 5 
{x² + y² = 5 

{(x + y) + xy = 5 
{(x + y)² - 2xy = 5 

Замена: 
x + y = a 
xy = b 

Тогда: 
{a + b = 5 
{a² - 2b = 5 

Ко второму уравнению прибавим первое, умноженное на 2 
a² - 2b + 2a + 2b = 5 + 10 
a² + 2a - 15 = 0 
a = -5 
a = 3 

{a = -5 
{a + b = 5 

{a = -5 
{b = 10 

{a = 3 
{a + b = 5 

{a = 3 
{b = 2 

Вернёмся к замене: 
Если: 
{x + y = 3 
{xy = 2 

{x = 3 - y 
{xy = 2 

y(3 - y) - 2 = 0 
y² - 3y + 2 = 0 
y = 1 
y = 2 

{xy = 2 
{y = 1 

{x = 2 
{y = 1 

{xy = 2 
{y = 2 

{x = 1 
{y = 2 

Если: 
{x + y = -5 
{xy = 10 
Решений нет. 

Ответ: 
{x = 1 
{y = 2 

{x = 2 
{y = 1